Draft Annual Plan (1995-96) Part II—A—Plan Proposals in Detail of (Sectors) (I)—Agriculture and Allied Activities (II)—Rural Development (III)—Special Area Programme Government of Goa - Planning Commission (Planning Commission, 1995)
With a view to maintain purity of seeds, quality paddy and pulse seeds would be provided to the farmers on 50% subsidised rates by bringing the same from the Research Institutes and various seed producing Corporations and Agencies, on selective basis and also by producing and multiplying at various Government Farms.
Government of Goa, Directorate of Planning, Statistics and Evaluation